DESIGN OF AUTOMATIC CHANGE OVER SWITCH (ACOS) PROTOTYPE USING MICROCONTROLLER BASED ON INTERNET OF THINGS (IOT) - Salsabillah, Chalwah Farida; Hartono, Hartono; Suyatmo, Suyatmo (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Electricity supply from PLN is not always stable and sometimes experiences interruptions due to problems in the transmission or distribution system of the main power source. To overcome this problem, a backup source such as PLTS is required. The Automatic Change Over Switch (ACOS) system is designed to detect failures and automatically switch to an alternative power source when a disconnection occurs. It allows switching from PLN power supply to solar panel automatically. This ACOS is controlled by Wemos and equipped with a PZEM-004T sensor. The system can be monitored and set up via an Internet of Things (IoT) Smartphone app in manual or automatic mode.